PENERAPAN METODE MUHASABAH AN-NAFS DALAM MENDISIPLINKAN PE& DIDIK DI MAS THAWALIB LUBUK JANTAN KABUPATEN TANAH DATAR - Winda Aulia Darmawis; Fauzan Fauzan (CV. ADIBA AISHA AMIRA, 2024)
The background to this research was because at Madrasah Thawalib there were many students who were not disciplined either in terms of time discipline or discipline when studying. However, after the implementation of the muhasabah an-nafs method, there was a change. Previously, many students were undisciplined, but now it is rare to find undisciplined actions. This research method uses a qualitative descriptive research method. Researchers collected data using the interview method. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Then carry out data validity by data triagulation. The research results show that the implementation of the Muhasabah An-Nafs method is carried out by implementing several stages, namely, designing the stages that will be implemented in its implementation and adapting them to the stages that commonly occur in the Muhasabah An-Nafs method. These stages are Takhalli, Tahalli and Tajalli. In this stage, students are invited to introspect on the mistakes they have made, then fill in their good identity by providing examples of positive behavior, teaching them what is good and what is not. After that, students admit their mistakes and try not to make mistakes again. After the muhasabah was held at MAS Thawalib Lubuk male, there were changes in the students who used to often violate school rules and regulations, but now they are rarely found. So that by implementing the muhasabah an-nafs method, students can be disciplined.